PENGEMBANGAN BRAILLE TALKING CALCULATOR BERBASIS MICROCONTROLLER SEBAGAI MEDIA BANTU HITUNG BAGI PENYANDANG TUNANETRA DI SLB A YAKETUNIS - Minarti Minarti; Very Erwina Safitri; Ritaudin Isnaini (Pelita - Jurnal Penelitian Mahasiswa UNY, 2012)
The research is aimed at developing a calculator integrated with the microcontrollerfacilitated with talking and Braille keypad for the blind.The method used in the research was Research and Development which consisted ofthe following steps proposed by Sugiono (2011): identifying potential and problems, collectingdata, designing the product, validating the product, revising the design, trying out the design,revising the product, trying out, revising the product.The result of the research was Braille Talking Calculator which was considered to befeasible as a functional calculating aid for the blind. In addition, it was also effective to improvethe efficiency of the calculating activity of the blind.Keywords: the blind, calculating aid, Braille Talking Calculator